1997
DOI: 10.1007/s002530051007
|View full text |Cite
|
Sign up to set email alerts
|

Axenic aerobic biofilms inhibit corrosion of SAE 1018 steel through oxygen depletion

Abstract: Corrosion inhibition of SAE 1018 steel by pure-culture biofilms of Pseudomonas fragi and Escherichia coli DH5 alpha has been evaluated in complex Luria-Bertani medium, seawater-mimicking medium, and modified Baar's medium at 30 degrees C. In batch cultures, both bacteria inhibited corrosion three to six fold compared to sterile controls, and the corrosion was comparable to that observed in anaerobic sterile media. To corroborate this result, a continuous reactor and electrochemical impedance spectroscopy were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0
2

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(46 citation statements)
references
References 16 publications
1
43
0
2
Order By: Relevance
“…A protective effect of Pseudomonas fragi and Escherichia coli DH5 was found by Jayaraman et al (13). Here, the formation of a biofilm was crucial, as oxygen depletion under the biofilm was responsible for the corrosion protection (12). However, the mechanical instability of biofilms was seen as a drawback for their technical application.…”
mentioning
confidence: 94%
“…A protective effect of Pseudomonas fragi and Escherichia coli DH5 was found by Jayaraman et al (13). Here, the formation of a biofilm was crucial, as oxygen depletion under the biofilm was responsible for the corrosion protection (12). However, the mechanical instability of biofilms was seen as a drawback for their technical application.…”
mentioning
confidence: 94%
“…Do istog zaključka došli su i Jayaraman sa saradnicima [26,35,36] u svojim istrazivanjima ispitujući koroziono ponašanje čelika (SAE 1018), bakra i aluminijuma [37] u prisustvu različitih bakterija (Bacillus brevis 18 i Pseudomonas fragi K). Uočeno je da bakterije Pseudomonas fragi i Escherichia coli DH5α formiraju zaštitni biofilm na površini čelika štiteći ga na taj način od korozije.…”
Section: Inhibicija Korozije Pomoću Biofilmaunclassified
“…Aerobna vrsta P. fragi kao i anaerobna E. coli proizvode biofilmove koji su se pokazali kao efikasni inhibitori korozije. Biofilm sintetisan od strane aerobne bakterijske vrste se pokazao efikasnijim što dovodi do zaključka da potrošnja kiseonika od strane bakterijske vrste ima značajnu ulogu u procesu korozije [26,35]. Kao potencijalni inhibitori korozije čelika pokazale su se i bakterijske vrste Chryseobacterium indolgenes MUT.2 i Klebsiella pneumonia MUT.1 koje formiraju zaštitni sloj na površini čelika [38].…”
Section: Inhibicija Korozije Pomoću Biofilmaunclassified
“…The rate of decline of trend line in each treatment was faster than their corresponding high concentration formulations; furthermore, sulfate concentration was much lower at the 10th day. The studies of Jayaraman et al (1997) showed that for some SRB, nitrite has effects on variable acid suppression and H 2 S removal in the bioreactor, while nitrate are not valid in these areas. Therefore, nitrite is more effective in preventing some high-temperature oil field from acidizing, because of its direct reaction with the sulfide and is proved to be an effective inhibitor of sulfatereducing long-term.…”
Section: Changes Of Sulfate Concentration In the Experiments To Whichmentioning
confidence: 99%